2021
DOI: 10.3390/ani11030651
|View full text |Cite
|
Sign up to set email alerts
|

A Freedom of Coxiella burnetii Infection Survey in European Bison (Bison bonasus) in Poland

Abstract: Q fever is an important zoonosis caused by the intracellular Gram-negative bacteria Coxiella burnetii. The source of infection are numerous species of mammals, birds, reptiles and amphibians, as well as ticks. The disease is widespread throughout Europe, but the role of wildlife in its epidemiology is poorly understood. The European bison (Bison bonasus) population has been growing European-wide quite dynamically over the last few years. The aim of this study was to determine whether C. burnetii infection occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, it should be stressed that such studies were conducted over 30 years ago and only within a single location, which was found to be self-limiting for Q fever. Our present findings, indicating that Q fever is not currently a threat to the European bison population, are in line with the latest reports on this topic in European bison [ 47 ]. Similarly, low prevalence levels have been recorded in other wild ruminants: 6.8% in European mouflon ( Ovis orientalis musimon ) and 2.4% in red deer ( Cervus elaphus ) in Spain [ 48 ] and 1.2% in roe deer in Flanders [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, it should be stressed that such studies were conducted over 30 years ago and only within a single location, which was found to be self-limiting for Q fever. Our present findings, indicating that Q fever is not currently a threat to the European bison population, are in line with the latest reports on this topic in European bison [ 47 ]. Similarly, low prevalence levels have been recorded in other wild ruminants: 6.8% in European mouflon ( Ovis orientalis musimon ) and 2.4% in red deer ( Cervus elaphus ) in Spain [ 48 ] and 1.2% in roe deer in Flanders [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…One of the tools that can be used to manage wildlife species is selective elimination (culling) of individuals, which genotype (and/or lineage) or health impairment make them undesirable in a herd. Apart from that, diseased individuals may threaten other animals in the population in case of contagious diseases, which, to make things worse, may also have zoonotic potential and be a challenge for public health [3,4]. This applies especially to tuberculosis, which is currently a real zoonotic health hazard in wild ruminant populations including European bison [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the bovine mycobacteria, as well as the atypical mycobacteria, were isolated from European bison kept in captivity in the area where bovine tuberculosis was diagnosed in the past [ 9 , 10 ]. In the serological survey of Q fever, antibodies against Coxiella burnetii were only found in a single free-living individual, suggesting that this disease is not currently a significant problem for the European bison’s health [ 11 ]. Other bacteria which may affect the European bison are Treponema spp., identified as a cause of digital dermatitis lesions [ 12 ]; Pasteurella multocida , associated with respiratory tract diseases [ 13 ] and Borrelia burgdorferi [ 14 ].…”
Section: Introductionmentioning
confidence: 99%